2010
DOI: 10.5194/amt-3-683-2010
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a portable gas phase standard generation and calibration system for volatile organic compounds

Abstract: Abstract. We report on the development of an accurate, portable, dynamic calibration system for volatile organic compounds (VOCs). The Mobile Organic Carbon Calibration System (MOCCS) combines the production of gas-phase VOC standards using permeation or diffusion sources with quantitative total organic carbon (TOC) conversion on a palladium surface to CO 2 in the presence of oxygen, and the subsequent CO 2 measurement. MOCCS was validated using three different comparisons: (1) TOC of high accuracy methane sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 22 publications
3
66
5
Order By: Relevance
“…Known mixing ratios of acetic acid were generated by diluting pure acetic acid emitted from a permeation tube (Kin-Tek Inc.) that was gravimetrically certified (103 ± 5 % ng min −1 at 30 • C) by the manufacturer. The high dilution flow rates yielded stable acetic acid calibration gas streams at low ppbv levels, within the range of those in ambient air, and much less than ppmv level standards typically generated by other techniques (Veres et al, 2010). The dilution flow (F dil ) was used to control the mixing ratio of acetic acid in the calibration gas.…”
Section: Permeation Systemmentioning
confidence: 99%
“…Known mixing ratios of acetic acid were generated by diluting pure acetic acid emitted from a permeation tube (Kin-Tek Inc.) that was gravimetrically certified (103 ± 5 % ng min −1 at 30 • C) by the manufacturer. The high dilution flow rates yielded stable acetic acid calibration gas streams at low ppbv levels, within the range of those in ambient air, and much less than ppmv level standards typically generated by other techniques (Veres et al, 2010). The dilution flow (F dil ) was used to control the mixing ratio of acetic acid in the calibration gas.…”
Section: Permeation Systemmentioning
confidence: 99%
“…9 To track system stability and repeatability, a signal calibration was performed periodically, before or after experiments, by flowing a steady concentration of diethylene glycol (DEG) for several minutes, which was quantified using a catalytic converter and CO 2 analyzer following the method of Veres et al 5 The instrument showed excellent stability and repeatability.…”
Section: No 3 --Cims Quantificationmentioning
confidence: 99%
“…The CO 2 was then measured using a LI-840A CO 2 analyzer (LI-COR). 5 The FIXCIT inlet was used in the calibrations to maintain the same f inlet values. Malonic acid (C 3 H 4 O 4 ) was the most sensitive organic compound tested and was used as the primary LVOC calibrant since it is thought to cluster at rates close to the collision limit 6 .…”
Section: No 3 --Cims Quantificationmentioning
confidence: 99%
“…A formic acid standard was added to the system to provide a baseline measure of instrument sensitivity throughout the biomass burning experiments and the subsequent laboratory studies of the inorganic acids. The formic acid source consisted of a thermostatted permeation tube that was routinely measured by catalytic conversion to CO 2 and non-dispersive infrared spectroscopy (NDIR) (Veres et al, 2010a). Nitric acid was also added to the system with a permeation tube, the calibration of which was accomplished by UV absorption spectroscopy as described by Neuman et al (2003).…”
Section: Ni-pt-cimsmentioning
confidence: 99%